Effects of modeling rote versus varied responses on response variability and skill acquisition during discrete‐trial instruction. Issue 2 (7th December 2018) - Peterson, Sean P.; Rodriguez, Nicole M.; Pawich, Tamara L.
Abstract : Despite its advantages, discrete‐trial instruction (DTI) has been criticized for producing rote responding. Although there is little research supporting this claim, if true, this may be problematic given the propensity of children with autism to engage in restricted and repetitive behavior. One feature that is common in DTI that may contribute to rote responding is the prompting and reinforcement of one correct response per discriminative stimulus. To evaluate the potential negative effects of rote prompts on varied responding, we compared the effects of modeling rote versus varied target responses during the teaching of intraverbal categorization. We also evaluated the effects of these procedures on the efficiency of acquisition of any one correct response. For all four children, any increase in varied responding was fleeting, and for two participants, acquisition was slower in the variable‐modeling condition.